Development and validation of RP-HPLC method for determination of some pesticide residues in apple samples - Velkoska-Markovska, Lenche; Ilievski, Ugrin; Jankulovska, Mirjana S.; Petanovska-Ilievska, Biljana (Akademiai Kiado Zrt., 2024)
Apples are among the most common fruits, produced on the territory of North Macedonia. Before they reach the market, it is essential to be tested for pesticide residues, which are used for protection against pests for this culture, and in order to ensure the customer safety. For this reason, a novel and simple method for simultaneous determination of captan, folpet, difenoconazole and chlorpyrifos in apple samples has been developed and validated. Acetone is used for extraction of the pesticide residues, followed by liquid-liquid (LLE) and solid–phase extraction (SPE). Separation and quantiﬁcation of analytes is achieved on reversed-phase high performance liquid chromatography (RP-HPLC) with UV diode array detector (UV-DAD). The best results are obtained using analytical column LiChrospher 60 RP-select B (250 mm 3 4 mm, 5 μm), with isocratic elution and acetonitrile/0.1 % acetic acid in water (70:30, V/V) as a mobile phase. The ﬂow rate is 1 mL min 1, and UV detection is performed at 220 and 230 nm. The linearity of the method is tested in the range of 1.50–3.60 mg kg 1 for captan and folpet, and 0.35 – 0.60 mg kg 1 for difenoconazole and chlorpyrifos. The obtained values for recovery and RSD ranged from 94.94 to 114.63 %, and 0.09–9.25 %, respectively. The validated method is successfully applied to apple samples for the determination of the investigated pesticide residues.
Keywords: RP-HPLC, UV-DAD, solid-phase extraction, pesticide residues, apples, validation method